2005
DOI: 10.4049/jimmunol.175.6.3681
|View full text |Cite
|
Sign up to set email alerts
|

Cysteine-Tailed Class I-Binding Peptides Bind to CpG Adjuvant and Enhance Primary CTL Responses

Abstract: Immunostimulatory CpG motifs in synthetic oligonucleotides can be effective adjuvants for the priming of CTLs. We first observed that a single male-specific peptide (KCSRNRQYL) (HY2) was more efficient than another male-specific peptide (WMHHNMDLI) (HY1) at priming IFN-γ-secreting CTLs in vivo when combined with lipid A and CpG and that it also visibly precipitated CpG. The addition of the six N-terminal residues (KCSRNR) from HY2 to HY1 yielded a peptide, KCSRNR-HY1, that both precipitated CpG and primed incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Phosphorothioate diesters have been described to react with activated disulfides such as the Ellman reagent, 4 most likely forming mixed thiol-thiophosphate disulfides. 5 Yet, phosphorothioate diesters have also been reported not to react with pyridyldisulfide groups. 6 In fact, there are various reports on the synthesis of disulfide-linked conjugates of phosphorothioated oligonucleotides, 7−9 showing that disulfides between two thiols can be formed in the presence of and with no interference from phosphorothioate groups.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Phosphorothioate diesters have been described to react with activated disulfides such as the Ellman reagent, 4 most likely forming mixed thiol-thiophosphate disulfides. 5 Yet, phosphorothioate diesters have also been reported not to react with pyridyldisulfide groups. 6 In fact, there are various reports on the synthesis of disulfide-linked conjugates of phosphorothioated oligonucleotides, 7−9 showing that disulfides between two thiols can be formed in the presence of and with no interference from phosphorothioate groups.…”
Section: ■ Introductionmentioning
confidence: 99%
“…1A). It remains unclear which of these two specificities constitutes the major response; D b -Uty + CTL are usually considered quantitatively and qualitatively superior [11,37,38], but other studies have found the converse, with D b -Smcy + CTL predominating [33,39]. The graphs at the top of Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, modulators of innate immune responses are now frequently being incorporated as ‘adjuvants’ to boost immunity to vaccines [54,55]. TLR ligands such as MPL and CpG‐ODN have been shown to be excellent vaccine adjuvants in animal studies, promoting development of robust antigen specific humoral and cellular responses [56–63]. Thus, immunomodulators used to boost innate immune responses in the urinary tract may be also employed to boost adaptive immune responses.…”
Section: Immunomodulation Of the Urinary Tractmentioning
confidence: 99%